THz Applications for the Engineering Approach to Modelling Frequency Dispersion within Normal Metals at Room Temperature - Lucyszyn,S; Zhou,Y (PIERS Online, 2010)
The use of the accurate classical relaxation-effect model for frequency dispersion innormal metals at room temperature with THz structures can be mathematically cumbersome andnot insightful. Recent work has demonstrated that it is possible to dramatically simplify otherwise complex analysis and allows for a much deeper insight to be gained into the classical relaxation-effect model. This paper gives applications for this engineering approach. Here, using the concept of Q-factor for a metal, the synthesized equivalent transmission line model is validated. Then, using the concept of complex skin depth, analysis is performed on hollow metal-pipe rectangular waveguides and their associated cavity resonators. This work proves that the mathematical modelling of THz structures can be greatly simplied by taking an electrical engineering approach to these electromagnetic problems.